Signal conditioning circuits for low vibration signals using an array of piezoelectric sensors. (2021) - Karbari, Sudha R.; Mohanram, Sreyas; Sriniketh, S.S.; Uttara Kumari, M.; Shireesha, G.
Abstract: Piezo-electric sensors have found widespread application today due to their ability to provide an interface between the mechanical and electronic world. For humans, in order to interact with these materials, we require an electronic interface. This paper describes one of the possible interfaces, which includes a charge amplifier cascaded with a filter circuit to obtain the frequency response. A novel circuitry consisting of a rectifier and comparator is used to identify the activated channels of the array of piezoelectric sensor. This signal conditioning circuit makes use of active devices such as op amps and nonlinear devices such as diodes along with passive components. The novel circuitry is designed for 2 channels, and demonstrates the logic of selection of these based on the signal parameters. This concept can be extended to any number of channels.